Tes Toleransi Glukosa Oral (TTGO) Pasca Pemberian Suspensi Kedelai Dibanding Suspensi Tempe pada Tikus (Rattus norvegicus Galur Wistar) Diabetik - Huriatul Masdar; Muhammad Radhiatul Hakiki; Muhammad Rafi Syahputra; Tommy Satriasumatri; Deskafiani Putri; Rizki Bunaya; Desby Juananda (Health and Medical Journal, 2021)
Introduction: Genistein, daidzein and glicytein are soybean’s isoflavones which have been known having anti diabetic effect. Fermentation process of soybean can lead to formation aglycan isoflavones which have higher bioavailability than unfermented-soybean. Aims: This research was aimed to evaluate the effect of soybean and tempeh (fermented-soybean) administration to oral glucose tolerance test (OGTT) in diabetic rats. Method: Twenty male Rattus norvegicus Wistar strains were used in this experiment, divided into 4 groups: standard, negative control, soybean and tempeh group. Type 2 diabetes in rats was induced by giving streptozotocin (50 mg/kgBW) and nicotinamide (110 mg/kgBW) intraperitoneally. Blood glucose were measured by using blood glucose test meter and classified into diabetes if its level above 200 mg/dL. Soybean (200 mg/kgBW/day) and tempeh (200 mg/kgBW/day) suspension were given by using gastric tube for 30 days. Results: The results showed the means of either fasting blood glucose (FBG) or 2 hours post prandial blood glucose (2hPP) of negative control were persistent above 200 mg/dL on day 15th and 30th  (p> 0,05). In soybean group there was a decrease the mean of FBG on day 15th  (p<0.05) but did not reach the normal level, and on day 30th the mean of FBG was <200 mg/dL (p<0.05) however 2hPP blood glucose was still >200 mg/dL (p<0.05). Furthermore, in tempeh group, the means of either FBG or 2hPP blood glucose reached the normal level in day 15th and 30th (p <0.05). Conclusion: the provision of tempeh was better in controlling blood sugar levels than soybean.